Use of meloxicam with or without dipyrone in non-surgical embryo recovery in hair sheep: Effects on animal welfare. - RIBEIRO, A. C. S. (2023)
Abstract: The aim of this study was to determine the effectiveness of meloxicam with or without dipyrone on the welfare of ewes subjected to non-surgical embryo recovery (NSER). Two studies were carried out using 51 multiparous Santa Inês ewes. All animals received a standard oestrous synchronization treatment and a superovulatory protocol. In Study 1, 12 ewes received meloxicam (GM) before cervical transposition (1 mg kg-1 , i.v.), repeated 24 h after (1 mg kg-1 , i.m.), while the other 10 received a saline solution, remaining as a control group (GC1). In Study 2, ewes were allocated into a group of 15 ewes treated as GM of Study 1 associated with dipyrone (GMD; 50 mg kg-1 , i.m.) before cervical transposition, 12 h, and 24 h after, or a control group (GC2) of 14 ewes treated with saline solution. In both studies, heart and respiratory rates (RR), cortisol, glucose, total proteins, albumin and globulins blood concentration were recorded before sedation (BS), after sedation (AS), after cervical transposition, immediately after collection (IAC), and 0.5, 1.5, 3, 6, 12, 24 and 48 h after embryo collection (hAC). In Study 1, RR tended to be greater in GC1 (p = .08), serum total proteins and globulins values were lower and serum albumin values were greater in this group than GM (p = .003, p < .0001, and p < .0001, respectively). In Study 2, treatment of GMD tended to reduce the glycaemia at AS (p = .052) and reduced it at 3hAC (p < .0001), and 6hAC (p = .03). It also tended to reduce cortisol concentrations (p = .10). The other variables varied with NSER without interaction with the experimental treatments. In conclusion, in this study condition, NSER in sheep induced transient changes indicative of stress and possibly pain, therefore, affecting animal welfare. The administration of meloxicam was ineffective to reduce those responses, and the association of dipyrone had only slight effects without modifying the main welfare indicative responses in ewes subjected to NSER.